The Exploration of Social Capital of the Religious Women Group in the Development of a Waste Bank in Banjar Serasan, East Pontianak - Arifin Arifin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Borneo Waste Bank is a waste bank program with excellent managerial and operational systems. This program was founded based on the joint initiation between mothers in the Religious Women Group (Indonesian: Kelompok Ibu-Ibu Pengajian) and members of Workgroup of Family Welfare Empowerment (Indonesian: Kelompok Kerja Pemberdayaan Kesejahteraan Keluarga (POKJA PKK)) in Banjar Serasan, East Pontianak. The Religious Women Group as the prime mover involved outside parties in developing the waste bank program, making the program grow. The purpose of this study was to explore social capital in the management of the Borneo Waste Bank. In this study, the researcher applied a descriptive-qualitative approach. Data were collected through in-depth interviews, observations, and documentation. The collected data were then verified, analyzed, and concluded. The results of this study indicated that the dominant social capital in driving the Borneo Waste Bank was the cooperation between husbands and wives who managed the waste bank. Husbands acted as a supporter and sought social networking with outside parties (third parties). The mothers who were members of the Religious Women Group maintained the sense of togetherness in managing the waste bank through religious gatherings for studying the Qur’an which was carried out regularly. The waste bank program that was running could survive and went well due to being built based on a high sense of togetherness through group activities outside the program that were carried out continuously. A social network underlain by the value of togetherness and a mission of social contribution was an important aspect in the development of a program.